The Distribution of Foreign Exchange Price Changes: Trading Day Effects and Risk Measurement - McFarland, James W.; Pettit, R. Richardson; Sung, Sam K. (Journal of Finance, 1982)
This study investigates the nature of price changes in a variety of major and minor foreign exchange markets. The results suggest that the log of price changes over one (trading) day intervals seems to follow a non-normal stable distribution function. Different measures of location (and to lesser extent scale) are present for different days of the week. Dollar denominated price changes are high on Mondays and Wednesdays and low on Thursdays and Fridays for all currencies. The Wednesday-Thursday result is consistent with the settlement procedures used in foreign exchange transactions in the dollar. The Friday-Monday result is consistent with an increase in demand for the dollar prior to the weekend.